GENETIC DIVERSITY OF AMPICILLIN-RESISTANT Vibrio ISOLATED FROM VARIOUS STAGES OF TIGER SHRIMP LARVAE DEVELOPMENT - WIDANARNI WIDANARNI; ANTONIUS SUWANTO (BIOTROPIA, 2000)
This research was carried  out to  study  genetic  diversity of ampicillin-resistant Vibrio  from various  stages of tiger  shrimp larvae  (Penaeus Monodon) development from,Tambak Inti Rakyat hatchery, near Labuan, West Java, Indonesia. A total of 25 ampicillin-resistant Vibrio isolates were isolated using thiosulphate  citrate bile-salt  sucrose  agar (TCBS-Agar) and seawater  complete agar (SWC-Agar). Physiological and biochemical characterization showed that the isolates could be grouped into only two species, i.e. V. harveyi from the egg stage; and V. metschnikovii from larvae and post-larval stage (i.e nauplius, zoea, mysis, PLi, PL5, PL,0, and PL,5). These isolates were also present in their respective rearing water  of  each stage  and  some natural feed.  Schizotyping analysis employing restriction endonuclease Noll (5'-GC4GGCCGC) indicated that the isolates could be grouped into  at least  13 different  genotypes.  Therefore,  schizotyping  was  more discriminative than physiological characterization. This study showed that particular groups of Vibrio colonized all stages of shrimp larvae and demonstrated closed phylogenetic relationship. These groups of Vibrio might be  the dominant microbiota which could suppress the development of other Vibrio including the pathogenic Vibrio. Key words : Shrimp/ampicillin-resistant K/fcno/schizotyping